Assessing Social Exclusion and Mobility in Brazil - Marió, Estanislao Gacitúa; Woolcock, Michael (Washington, DC: World Bank, 2012)
Inequality, exclusion and lack of mobility are unfortunate characteristics of life for Brazil's poorest and minority citizens. It is a pervasive and debilitating problem that is perceived to be the result of fair rules but poor administration. Policy changes are needed to ensure fair opportunities for everyone. These include ensuring fair access to labor markets, facilitating access to assets such as land, expanding and improving social security, building human capital, focusing on youth, decreasing race inequality and discrimination, and strengthening participation and citizenship.